Lost economic output due to high bureaucratic burden - Oliver Falck; Yuchen Guo; Christian Pfaffl (EconPol Forum, 2024)
This study examines the overall economic costs arising from high levels of bureaucracy. We also shed light on whether and to what extent the digitalization of administrative processes can reduce the economic costs of bureaucracy.The results of our international analysis show that a fundamental reduction in bureaucracy is accompanied by a 4.6-percent average increase in real GDP per capita. If Germany had implemented a fundamental reduction in bureaucracy in 2015, GDP per capita would have been EUR 2,449 higher in 2022. On average for the years 2015 to 2022, this would have corresponded to an annual increase in real GDP per capita of EUR 1,766, or EUR 146 billion in total per year. Our results also show that a digitalization push in public administration can increase the level of real GDP per capita by 2.7 percent while maintaining the same level of bureaucracy. The positive impact of digitalization is particularly strong in countries with high levels of bureaucracy.
Keywords: 330